THE STRUCTURAL AND STYLISTIC FUNCTION OF THE REMARK IN THE SHORT STORIES OF VASYL STEFANYK - Visych, oleksandra (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2023)
The article attempts to analyze and typologies the remark in prose by Vasyl Stefanyk, which is considered in the context of the trends of the tragedization of the epic that became dominant in the late 19th and early 20th centuries. The purpose of the study is to identify the author’s specificity of constructing a dramatic remark in the writer’s short stories, and to outline its function in dramatizing the narrative. In this light, the remark, as the territory of the author’s voice, turns out to be a structural and stylistic element of the prose text that contributes to the theatricalization of the narrative. As well it is also a means of psychological and emotional expression, an element of visualization of the main text, and contributes to its polyphony. The study proves that Stefanyk’s short fiction is a unique form of theatricality in which the remark has an important function. The author manifests himself in the text with the help of epic and lyricized remarks, which are presented in the works to varying degrees, contain emotional and psychological accents, record non-verbal communication, outline mise-en-scene, etc. The multifunctionality and typological diversity of the theatrical remark in text by Vasyl Stefanyk are noted. Novelty. The article characterizes the multifunctionality and typological diversity of the theatrical remark in the prose by Vasyl Stefanyk. The method of analysis used can be productive for further studying of the techniques of dramatization of prose texts.